2023
DOI: 10.1038/s41398-023-02435-0
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3, multicenter, double-blind, randomized, placebo-controlled clinical trial to verify the efficacy and safety of ansofaxine (LY03005) for major depressive disorder

Abstract: Major depressive disorder (MDD) is the most prevalent form of depression and is becoming a great challenge for public health and medical practice. Although first-line antidepressants offer therapeutic benefits, about 35% of depressed patients are not adequately treated, creating a substantial unmet medical need. A multicenter, double-blind, randomized, placebo-controlled phase 3 clinical trial was conducted in patients with MDD in China to assess the efficacy and safety of ansofaxine (LY03005), a potential tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…These rates were comparable to those reported in a previous study including SSRIs, SNRIs and the novel antidepressants vortioxetine and vilazodone (the response rate was 53–74%, and the remission rate was 31–46%). 2931 However, the improvements in the placebo group (least-squares mean difference in change, 14.51) were higher than those seen in another study (least-squares mean difference in change: −11.0, 32 −10.3, 33 respectively), suggesting a slightly stronger placebo effect.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…These rates were comparable to those reported in a previous study including SSRIs, SNRIs and the novel antidepressants vortioxetine and vilazodone (the response rate was 53–74%, and the remission rate was 31–46%). 2931 However, the improvements in the placebo group (least-squares mean difference in change, 14.51) were higher than those seen in another study (least-squares mean difference in change: −11.0, 32 −10.3, 33 respectively), suggesting a slightly stronger placebo effect.…”
Section: Discussionmentioning
confidence: 62%
“…35 In contrast, the 1.23% rate of discontinuation due to AEs for the placebo group in our trial was lower than the 4% average reported for the placebo arms in that same meta-analysis. Additionally, when comparing Anyu Peibo capsules to other commonly prescribed antidepressants, the discontinuation rate for venlafaxine (37.5–225 mg/day) was 12%, while for desvenlafaxine, the discontinuation rates were 4.1% 31 at 50 mg/day and 8.5% at 100 mg/day. For vortioxetine, the discontinuation rates were 5%, 6%, 8%, and 8% for doses of 5, 10, 15, and 20 mg/day, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations